Pain in osteochondral lesions of the ankle: an investigation based on data from the German cartilage registry (KnorpelRegister DGOU) = Schmerz bei osteochondralen Läsionen des Sprunggelenks : eine Auswertung aus dem Knorpelregister der Deutschen Gesellschaft für Orthopädie und Unfallchirurgie (KnorpelRegister DGOU) - Körner, Daniel; Bangert, Yannic (Zeitschrift für Orthopädie und Unfallchirurgie, 2018)
The aim of the study was to investigate parameters influencing the preoperative pain intensity in patients with osteochondral lesions of the ankle. The evaluation covered patient-related parameters such as age, sex, body mass index (BMI), as well as defect-related parameters, such as localisation, size and stage (according to the classification of the International Cartilage Repair Society [ICRS] and the Berndt-Harty-Loomer classification). We also examined the correlation between the different surgical techniques and additional factors, such as debridement of an impingement or stabilisation of the ankle on the one hand, and the preoperative pain intensity on the other.
Gesehen am 05.12.2019